BRITISH INDIRECT RULE AND ISLAM IN NORTHERN NIGERIA (1900-1940) - Hallouch, Nadjouia (PEOPLE: International Journal of Social Sciences, 2018)
When discussing European colonialism throughout history, one can never deny its impact upon the traditional religion of the colonized peoples. Europeans had always considered their colonial domination as being a “civilizing mission” which was based on the Christian principles and could not be achieved without challenging the traditional religion. Such colonists, who were eager to spread their Christian faith, found that the Christian missions were the main agents for conversion. These missions started first to convert the rulers by introducing new Christian ideas and principles. Once these rulers were converted, adherence of the ordinary people was a very easy task. When so doing, the Europeans succeeded to abolish the religious fundamentals of the traditional society. For instance in Togo and Ivory Coast, Christianity succeeded to gain a footing among their peoples and had a considerable position. This was not the pattern in Northern Nigeria, because despite the imposition of a series of reforms based on the Christian principles by the British through the Indirect Rule system, Islam continued to spread during the colonial era. The objective of this research paper is to look for the factors that contributed to the propagation of Islam in spite of the dominating foreign ideology and religion. For this end, it is necessary to examine the Fulani Islamic system, the Caliphate under colonial rule and the spread of Islam under British domination .It is concluded that through the maintenance of Quranic schools, restriction in the missionaries’ activities and the opening of major trade routes, the British helped a great deal the preservation of Islam and its continued expansion among the non- Muslims. British educational policy in Northern Nigeria after 1940 can be the object of another paper.